A full genome search in multiple sclerosis. - Ebers, G; Kukay, K; Bulman, D; Sadovnick, A; Rice, G; Anderson, C; Armstrong, H; Cousin, K; Bell, R; Hader, W; Paty, D; Hashimoto, S; et al. (1996)
The aetiology of multiple sclerosis (MS) is uncertain. There is strong circumstantial evidence to indicate it is an autoimmune complex trait. Risks for first degree relatives are increased some 20 fold over the general population. Twin studies have shown monozygotic concordance rates of 25-30% compared to 4% for dizygotic twins and siblings. Studies of adoptees and half sibs show that familial risk is determined by genes, but environmental factors strongly influence observed geographic differences. Studies of candidate genes have been largely unrewarding. We report a genome search using 257 microsatellite markers with average spacing of 15.2 cM in 100 sibling pairs (Table 1, data set 1 - DS1). A locus of lambda>3 was excluded from 88% of the genome. Five loci with maximum lod scores (MLS) of >1 were identified on chromosomes 2, 3, 5, 11 and X. Two additional data sets containing 44 (Table 1, DS2) and 78 sib pairs (Table 1, DS3) respectively, were used to further evaluate the HLA region on 6p21 and a locus on chromosome 5 with an MLS of 4.24. Markers within 6p21 gave MLS of 0.65 (non-significant, NS). However, D6S461, just outside the HLA region, showed significant evidence for linkage disequilibrium by the transmission disequilibrium test (TDT), in all three data sets (for DS1 chi2 = 10.8, adjusted P < 0.01)(DS2 and DS3 chi2 = 10.9, P < 0.0005), suggesting a modest susceptibility locus in this region. On chromosome 5p results from all three data sets (222 sib pairs) yielded a multipoint MLS of 1.6. The results support genetic epidemiological evidence that several genes interact epistatically to determine heritable susceptibility.